UJI EFEKTIFITAS SAMPAH PANGAN DAN NON PANGAN DALAM MENGHASILKAN BIOETANOL GENERASI KE DUA - Mohammad Rio Panca Anugrah Indri Sriwulan; Novirina Hendrasarie (EnviroUS, 2021)
Waste management and processing that is not optimal causes accumulation of waste every day. In addition, processing waste, especially plantation or agricultural waste that only becomes fertilizer or compost, will be very unfortunate. Cellulose waste can actually be used to create second generation bioethanol. With the use of as much as 20 grams of starting material, and a preliminary process such as delignification, it is intended that the lignin content in each material can be damaged and later the cellulose compound can be processed into glucose. Combination of treatments and materials such as corn cobs, skin of kluwek , used hvs paper, and used newsprint; NaOH liquid in the delignification process for 4 hours at 50 ° C; use of cellulose solution in the hydrolysis process for 4 hours at 50 ° C; variations in the addition of a solution of 10 ml v/v, & 20 ml v/v; variations long fermentation time 5 days, 10 days 15 days; and the distillation process is intended so that researchers get the highest alcohol content in the material and process being carried out. The best results were obtained on hvs paper material which was delignified first, and with the addition of a starter solution of 20 ml v/v, and fermentation time of 10 days with an alcohol content of 23.78%. Keywords: second generation bioethanol, delignification, fermentation